High-Throughput Characterization of Pt Supported on Thin Film Oxide Material Libraries Applied in the Oxygen Reduction Reaction - Schäfer, Dominik (2011)
Thin film metal oxide material libraries were prepared by sputter deposition of nanoscale Ti/Nb precursor multilayers followed by ex situ oxidation. The metal composition was varied from 6 at.% Nb to 27 at.% Nb. Additionally, thin wedge-type layers of Pt with a nominal thickness gradient from 0 to 5 nm were sputter-deposited on top of the oxides. The materials libraries were characterized with respect to metallic film composition, oxide thickness, phases, electrical conductivity, Pt thickness, and electrochemical activity for the oxygen reduction reaction (ORR). Electrochemical investigations were carried out by cyclic voltammetry using an automated scanning droplet cell. For a nominal Pt thickness >1 nm, no significant dependence of the ORR activity on the Pt thickness or the substrate composition was observed. However, below that critical thickness, a strong decrease of the surface-normalized activity in terms of reduction currents and potentials was observed. For such thin Pt layers, the conductivity of the substrate seems to have a substantial impact on the catalytic activity. Results from X-ray photoelectron spectroscopy (XPS) measurements suggest that the critical Pt thickness coincides with the transition from a continuous Pt film into isolated particles at decreasing nominal Pt thickness. In the case of isolated Pt particles, the activity of Pt decisively depends on its ability to exchange electrons with the oxide layer, and hence, a dependence on the substrate conductivity is rationalized.